Civility On Social Media (The Tendency Of Politeness Level Of Internet Users On Social Media ) - Mulyana, Ahmad; Morissan, Morissan (2015)
Social media is a boundless space of expression. Various ideas are able to be presented by its users own way, so that it appears to be unpredictable phenomena. News on social media evolve in such a way. Even the news about the president addressed immodestly. Based on the content that is the analyzed to determine the extent of thelevel of civility in social media.The results showed that (1)The average percentage news commentary assessed manners are as much as 74 percent while the average percentage of news comments judged to be polite is as much as 26.3 percent.